Airports' public infrastructure and sources of inefficiency - Ane Elixabete Ripoll-Zarraga (Journal of Economics, Finance and Administrative Science, 2023)
Purpose -The Spanish airport system contains several regional airports within an amenity distance and alternative travel modes. Profitable airports cross-subsidise small airports, which are not required for regional development or connectivity. Airports are government-owned and centralised-managed by Spanish Airports and Air Navigation (AENA, for its Spanish acronym). This study aims to analyse the probability of an under-used public infrastructure and the AENA's managerial ability as per the financial sustainability of the network in the long term. Design/methodology/approach - The national regulatory framework determines the airports' environment. Six airports revealed unobserved heterogeneity, avoiding model misspecification. The framework is defined through proxies of the singularities of the Spanish framework: public investments and geographical specifications. The stochastic frontier analysis model follows two time-varying specifications, accounting for airports' environmental factors, to ensure the robustness of the results to differ from the inefficiency caused by AENA and external factors. Findings - Airports' infrastructure capacity and traffic are not correlated; regional airports become a financial burden for the system unless they specialise or differentiate. Proxies defining the airports' context are relevant. Because airports do not compete for airlines and passengers, there are too many regional airports with little traffic, resulting in disused public infrastructure that falls far short of improving connectivity and regional development. Originality/value - This study contributes to paying attention to the characteristics of the regulatory framework, such as management strongly centralised in AENA, airport charges decided by the owner, lack of competition and lack of an independent regulatory entity. Another original contribution considers reliable capital measures (airports' infrastructure).
Keywords: H5; M21; L9; R4; 330; Stochastic frontier analysis (SFA); Environmental variables; Fixed effects; Catchment areas; AENA; Airports